2014
DOI: 10.3109/10799893.2014.948555
|View full text |Cite
|
Sign up to set email alerts
|

The NR4A orphan nuclear receptors: mediators in metabolism and diseases

Abstract: The NR4A subfamily is orphan nuclear receptors that belong to the larger nuclear receptors (NRs) superfamily of eukaryotic transcription factors. The NR4A subfamily includes three members, namely Nur77 (NR4A1), Nurr1 (NR4A2) and Nor1 (NR4A3) which are gene regulators and participate in diverse biological functions. Though the ligands for these receptors are presently unidentified, they are thought to be constitutively active. NR4A acts as molecular switches in gene regulation and their action is increasingly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 36 publications
2
55
0
Order By: Relevance
“…An increasing number of studies have demonstrated that NR4A receptors play important roles in the development of various cardiovascular diseases, including atherosclerosis, restenosis, angiogenesis, and heart failure (32,34,36). Previously, our studies identified Nur77 as a novel negative regulator for the β-AR-induced cardiac hypertrophy through inhibiting the NFATc3 and GATA4 transcriptional pathways (28).…”
Section: Discussionmentioning
confidence: 81%
“…An increasing number of studies have demonstrated that NR4A receptors play important roles in the development of various cardiovascular diseases, including atherosclerosis, restenosis, angiogenesis, and heart failure (32,34,36). Previously, our studies identified Nur77 as a novel negative regulator for the β-AR-induced cardiac hypertrophy through inhibiting the NFATc3 and GATA4 transcriptional pathways (28).…”
Section: Discussionmentioning
confidence: 81%
“…Organ damage Apoptosis Senescence disease notably diabetes, Parkinson and cardiovascular disease [24,28,40,41]. Several points of evidence underly the role of NR4A receptors in metabolic syndrome and diabetes.…”
Section: Metabolic Alteraɵonsmentioning
confidence: 99%
“…They were first identified molecularly as immediate-early response genes [212]. Much of the work on this gene class has focused on cell biological studies of their role in metabolism, cell cycle control, and apoptosis [213-215]. Nur77 interacts with RXR and p53 to regulate genes associated the cellular proliferation and participates with RXR and Bcl-2 in regulating apoptosis via a non-transcriptional pathway [214].…”
Section: Hr38/nhr-6/nur77/nurr1/nor1 (Nr4a)mentioning
confidence: 99%